Work Stress Levels At Madrasah Tsanawiyah Arrukhshatul'ulum: The Challenges of Digitalization in Developing Islamic Educational Institutions - Fauzi, Helmi Al Hafid; Hidayat, Wahyu; Ibnu Imam Al Ayyubi; Nurhikmah; Raed Awadh Saeed Al-Ghatnaini (Mudir : Jurnal Manajemen Pendidikan, 2025)
Madrasah Tsanawiyah Arrukhshatul'ulum an Islamic educational institution in Indonesia is facing an era of digitalization that forces every academic institution to adapt to technological developments. This research aims to explore the extent of the impact of digitalization on the work stress levels of teaching staff at Madrasah Tsanawiyah Arrukhshatul'ulum. This research uses quantitative and qualitative approaches to provide a more comprehensive analysis. The population in this study was all teachers at Madrasah Tsanawiyah Arrukhshatul'ulum, totaling 14 people, namely 10 permanent teachers and 4 contract teachers. The instrument used was a Likert questionnaire to measure work stress by analyzing data using descriptive statistics and interviews. In this research, it can be concluded that digitalization at Madrasah Tsanawiyah Arrukhshatul'ulum has had a significant impact on the welfare of teaching staff, with the majority of teachers (65%) reporting work stress levels in the medium category, which indicates that they are still in the adaptation phase to the demands of digitalization. However, this condition should not be ignored, because without appropriate intervention, stress levels can increase to the high category, as experienced by 20% of respondents. As many as 80% of teachers feel that they do not have sufficient skills to use digital devices, so they face difficulties in carrying out their duties. In addition, 70% of teachers stated that digital-based administrative burdens, such as filling in data via applications or electronic reports, were felt to have added to their work pressure.